The Republic. - Plato (Crofts classics., 2014)
This highly regarded volume features a modern translation of all ten books of The Republic along with a synoptic table of contents, a prefatory essay, and an appendix on The Spindle of Necessity by the translator and editor, Raymond Larson. Also included are an introduction by Eva T. H. Brann, a list of principal dates in the life of Plato, and a bibliography.